A glimpse of the limits of the European economic governance through the legislative and jurisprudential route of the "after-Weimar" German "economic constitution" - Damiano Censi (Cuadernos Electrónicos de Filosofía del Derecho)
The aim of this research is to reconstruct the actual limits of the legal framework of the management of public finances in the European Monetary Union, using the perspective of the path of the after-Weimar” German “economic constitution”. The EU federative process doesn’t present the same legal characteristics of any other, including the German one.  Nevertheless, some problems are necessarily similar, and similar solutions may be found. Consequently, this paper focuses on the succession of reforms in European economic governance since 2008 analyzing, in particular, the theme of sharing debt liabilities at a European level trough the dialogue between the Bundesverfassungsgericht and the EU institution.